2018
DOI: 10.1111/ssqu.12548
|View full text |Cite
|
Sign up to set email alerts
|

Racial Minorities’ Trust in Government and Government Decisionmakers

Abstract: Objective Compare the impact of being a racial minority for influencing political trust as measured by the standard, NES‐developed measures with its impact on assessments of the capacity of decisionmakers to make racially unbiased spending and hiring decisions. Additionally, to examine the political trust of American Indians, an understudied racial minority. Methods Bivariate and multivariate analysis of 2004 and 2008 National Annenberg Election Study survey data. Results Self‐designation as a racial minority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Tailored educational materials can raise awareness, encourage protective behaviors, and relieve stress and anxiety by informing and empowering the community. The integration and collaboration of governmental and non-governmental entities are essential to building and strengthening community resilience [44] and build trust with minorities that often mistrust government and medical systems [48][49][50]. Moreover, the relationships between organizations and individuals can play a significant role in building social connectedness, further contributing to the resilience of a community [44].…”
Section: Discussionmentioning
confidence: 99%
“…Tailored educational materials can raise awareness, encourage protective behaviors, and relieve stress and anxiety by informing and empowering the community. The integration and collaboration of governmental and non-governmental entities are essential to building and strengthening community resilience [44] and build trust with minorities that often mistrust government and medical systems [48][49][50]. Moreover, the relationships between organizations and individuals can play a significant role in building social connectedness, further contributing to the resilience of a community [44].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from political science emphasizes the importance of diversity for political trust. For example, Koch (2019) [63] shows that racial minorities anticipate a racial basis by White political elites when it comes to policy-making. Shared experiences between people and elites -be they scientists or politicians-may help facilitate trust [64] and increase support for policies.…”
Section: Plos Onementioning
confidence: 99%
“…While pathbreaking, the number of useable survey responses was fairly low (118 out of 480 randomly selected tribal officials). Another study (Koch, 2018), using NAES data, found levels of political distrust among American Indians/Alaska Natives was higher than among whites, but lower than among other racial minorities. His study, however, utilized data from the NAES' small number of self-identified American Indian/Alaska Native respondents.…”
Section: Political Trustmentioning
confidence: 98%
“…However, studies have found that political trust among some racial/ethnic minorities is low, although it is unclear how much of the disaffection goes beyond unhappiness with specific policies and officials. African Americans consistently evince greater levels of political distrust than whites (Aberbach and Walker, 1970;Avery, 2009;Shingles, 1981), but researchers have gotten mixed results from studies of Latinos (Abrajano and Michael Alvarez, 2010a;Abrajano and Michael Alvarez, 2010b;Koch, 2018).…”
Section: Political Trustmentioning
confidence: 99%